LITERATUR REVIEW: PENGARUH FOTOTERAPI TERHADAP NEONATUS DENGAN HIPERBILURUBIN - Munir, Zainal (Jurnal Keperawatan Profesional, 2023)
Hyperbilirubin is an excessive level of bilirubin in the blood with an amount of more than 10 mg% in the first week which causes jaundice or yellow color in infants to be clearly visible on the skin, sclera, mucosa, urine, and several others. organs, while the normal level of total bilirubin in infants is normal. infants, namely 5 mg% (Sembiring, 2019). Hyperbilirubinemia is the term used for neonatal jaundice after laboratory results show an increase in bilirubin levels. This hyperbilirubinemia can be caused by physiological and pathological processes (Sukadi; 2012 cited by Saptanto; 2016). Objective: To present a review and also a summary of phototherapy therapy in neonates with hyperbilirubinemia and provide an explanation of the therapies that can be performed in neonates with hyperbilirubinemia based on current evidence. Method: database search includes Google Scholar, Science Direct and Proquest with keywords phototherapy and hyperbilirubin Results: An analysis of 10 journals, 8 national journals and 2 international journals as well as 5 books showed that phototherapy was effective in reducing bilirubin levels in hyperbilirubin newborns. Conclusion: All interventions from this literature review were phototherapy efficacy in neonates with hyperbilirubinemia.